2005
DOI: 10.1088/0953-8984/17/48/017
|View full text |Cite
|
Sign up to set email alerts
|

Novel spin lattice in Cu3TeO6: an antiferromagnetic order and domain dynamics

Abstract: We report on the magnetic properties of an insulating cubic compound Cu3TeO6 studied by ac and dc susceptibility, torque magnetometry and neutron powder diffraction. A novel three-dimensional magnetic lattice composed of almost planar regular hexagons of Cu2+ S = 1/2 spins is present in Cu3TeO6. The magnetic susceptibility in the paramagnetic state obeys the Curie–Weiss law in the 200–330 K regime with ΘCW = −148 K and at TN = 61 K system undergoes an antiferromagnetic phase transition. Above TN the susceptib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
90
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(112 citation statements)
references
References 4 publications
19
90
3
Order By: Relevance
“…As of the last decade, the copper tellurate Cu 3 TeO 6 with a bixbyite structure a= 9.537 Å has been the focus of intense studies due to its unique magnetic spin‐web structure driven by the ordering of spin of 3d 9 copper and the proof of topological magnons for the first time in a 3D antiferromagnet . The nearest neighbour copper ions (≈3.18 Å) form a 3D network of 8 corner sharing hexagons centered around Te 6+ in the lattice.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…As of the last decade, the copper tellurate Cu 3 TeO 6 with a bixbyite structure a= 9.537 Å has been the focus of intense studies due to its unique magnetic spin‐web structure driven by the ordering of spin of 3d 9 copper and the proof of topological magnons for the first time in a 3D antiferromagnet . The nearest neighbour copper ions (≈3.18 Å) form a 3D network of 8 corner sharing hexagons centered around Te 6+ in the lattice.…”
Section: Introductionsupporting
confidence: 89%
“…All adjacent hexagons are oriented differently in space which results in 4 unique AFM domains below T c =61 K. When taking into account exchange with the second nearest neighbours (≈3.6 Å) a frustrated triangular sub‐lattice is formed which forms a pseudo‐Kagome type lattice that could prevent AFM ordering. Studies concluded that this exchange interaction must be significantly weaker than the nearest neighbour exchange and should only produce a slight tilting of the spin orientation . Inelastic neutron scattering studies showed that super‐super exchange (Cu‐O‐O‐Cu) through the 9 th nearest neighbour contributed significantly to the stability of the magnetic structure with an exchange energy comparable to the first nearest neighbour exchange .…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…in CuGeO 3 below the spinPeierls transition. 11 Therefore, we will concentrate in the following on the temperature regime above 20 K. In the investigated temperature regime the g values are practically temperature independent with g a * = 2.27(2), g b = 2.11 (3), and g c = 2.10(2), where a * denotes the direction perpendicular to the b-c plane. Such g values slightly enhanced with respect to the spin-only value of g = 2 are typical for the 3d 9 electronic configuration of Cu 2+ in distorted oxygen octahedra, where the orbital momentum is nearly quenched by the crystal field.…”
Section: Resultsmentioning
confidence: 99%